PERSEPSI MAHASISWA TERHADAP PROGRAM ENGLISH FOR INTERNATIONAL COMMUNICATION DI UNIVERSITAS MURIA KUDUS - Nuraeningsih, Nuraeningsih; Nurcahyo, Agung Dwi (Universitas Muria Kudus, 2023)
The purpose of this study is to describe students' opinions about the English for International Communication (EIC) program, which is followed by students of Universitas Muria Kudus (UMK) and managed by UPT Bahasa. The method of this research is descriptive research with a survey method by distributing questionnaires to 800 students who participated in the EIC program in 2019 from 13 undergraduate study programs in the UMK environment, but there were only 665 respondents who filled out. The questionnaire contains 14 closed-question items, which include teaching methods, teaching materials, media used, evaluation as well as interest and mastery of the material. used, evaluation as well as interest and mastery of the material. In addition, there is a special item that asks about native speakers as the EIC teaching team. The data collected was then analyzed based on the theme by using percentages. The data was then analyzed based on theme of the question items and made a percentage. The finding shows that they have a positive perception of the EIC program, particularly on the aspects of motivating students, teaching method, teaching media, and native teacher. Some recommendations are proposed for the university to make the program better in the future.